1997
DOI: 10.1007/pl00006989
|View full text |Cite
|
Sign up to set email alerts
|

Mode of Action of Herbicidal Derivatives of Aminomethylenebisphosphonic Acid. Part II. Reversal of Herbicidal Action by Aromatic Amino Acids

Abstract: The herbicidal action of N-pyridylaminomethylenebisphosphonic acids is accompanied by an impairment of anthocyanin biosynthesis. This suggests that they might act as inhibitors of some steps in aromatic amino acid biosynthesis. Herbicidal effects were reversed by aromatic amino acids using both bacterial and plant models, a finding that strongly supports this hypothesis. Structural features of these compounds suggest the sixth enzyme in the shikimate pathway 5-enolpyruvoylshikimate-3-phosphate (EPSP) synthase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 8 publications
1
23
0
2
Order By: Relevance
“…'Wisconsin') plants caused by glyphosate and N -pyridylaminomethylenebisphosphonic acids. Herbicidal effects were reversed by aromatic amino acids using both bacterial and plant models, a finding that strongly supports this hypothesis (Forlani et al, 1997).…”
Section: Introductionmentioning
confidence: 61%
“…'Wisconsin') plants caused by glyphosate and N -pyridylaminomethylenebisphosphonic acids. Herbicidal effects were reversed by aromatic amino acids using both bacterial and plant models, a finding that strongly supports this hypothesis (Forlani et al, 1997).…”
Section: Introductionmentioning
confidence: 61%
“…Thus the occurrence of a target in plant aromatic metabolism was investigated. While in vitro activity of EPSPS was found to be unaffected (Forlani et al 1997), that of the plastidic and Mn ++ -stimulated isoform of the first enzyme in the shikimate pathway, 3-deoxy-D-arabinoheptulosonate-7-phosphate synthase (DAHPS, EC 4.1.2.15), was markedly reduced. A kinetic analysis indicated that the most effective compound N-2-(5-chloro-pyridyl)aminomethylene bisphosphonic acid (Cl-pyr-AMBPA) inhibits enzyme activity competitively with respect to the substrate erythrose-4-phosphate (E4P), ruling out the possibility of an inhibition simply based upon its metal-chelating properties (Forlani et al 1996).…”
Section: Introductionmentioning
confidence: 98%
“…Esses mesmos resultados foram confirmados por Santos et al (2005), os quais descreveram que a adição desses aminoácidos aromáticos ao meio de cultura com B. japonicum preveniu a inibição do crescimento pelo glyphosate, pelo fato de esse microrganismo possuir esta enzima sensível ao glyphosate (Moorman et al, 1992;De Maria et al, 2006). Forlani et al (1997) também relatam que a adição de aminoácidos aromáticos preveniu parcialmente a inibição do crescimento de raízes de pepino (Cucumis sativus) causada pelo glyphosate e pelo ácido N-pirimidilaminometilenobifosfônico (Forlani et al, 1997).…”
Section: Introductionunclassified